2006
DOI: 10.1073/pnas.0505903103
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations are established in human colonic stem cells, and mutated clones expand by crypt fission

Abstract: The understanding of the fixation of mutations within human tissues and their subsequent clonal expansion is a considerable problem, of which little is known. We have previously shown that nononcogenic mutations in the mitochondrial genome occur in one of a number of morphologically normal colonic crypt stem cells, the progeny of which later occupy the whole crypt. We propose that these wholly mutated crypts then clonally expand by crypt fission, where each crypt divides into two mutated daughter crypts. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
280
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(299 citation statements)
references
References 29 publications
11
280
1
2
Order By: Relevance
“…Clonal expansion, equivalent to extreme segregation, of one of these mtDNA alterations has been shown to be at the basis of the observed OXPHOS defect in muscle [27,28], colon [29] and brain [30]. These studies confirmed that the threshold mutation proportion, inducing OXPHOS defect, was very high, often close to homoplasmy.…”
Section: Clinical Observationsmentioning
confidence: 56%
“…Clonal expansion, equivalent to extreme segregation, of one of these mtDNA alterations has been shown to be at the basis of the observed OXPHOS defect in muscle [27,28], colon [29] and brain [30]. These studies confirmed that the threshold mutation proportion, inducing OXPHOS defect, was very high, often close to homoplasmy.…”
Section: Clinical Observationsmentioning
confidence: 56%
“…Similar to q 0 cells that completely lack mtDNA, the reverse action of adenine nucleotide translocase and proton translocating ATPase can keep in respiration incompetent mitochondria the mitochondrial membrane potential high by using the remaining ATP supply of the cell (produced by glycolysis). This would explain why high levels of pathogenic mtDNA mutations can easily accumulate in colon crypts (76) or in skeletal muscle fibers having a high glycolytic activity. In neurons, which cannot compensate easily the lacking ATP supply of oxidative phosphorylation by glycolysis, it appears more likely that mitochondria with high loads of pathogenic mutations approach a state of decreased membrane potential making them potential targets for quality control on the organelle level.…”
Section: Genetic Mechanisms Explaining Disease Progressionmentioning
confidence: 99%
“…Mostly, non-synonymous substitutions causing aminoacid change in MT-CO1 and MT-CO2 were only found in MUTYH-associated-polyposis lesions, both adenomas and carcinomas. Mutations targeting these genes and leading to aminoacid changes have previously been found in colorectal cancer, 30 while data concerning mitochondrial DNA mutations in colorectal adenomas are extremely scanty. Sui and coworkers, 20 performing a whole genome analysis of mitochondrial DNA from gastrointestinal precancerous lesions, including sporadic colorectal adenomas, found MT-CO1 among the most frequently mutated sequences.…”
Section: M1mentioning
confidence: 99%